Relative ranks in the monoid of endomorphisms of an independence algebra - Mitchell, James D. (2011)
The relative ranks of the monoid of endomorphisms of a strong independence algebra of infinite rank modulo two distinguished subsets are calculated. These subsets are the group of auto- morphisms and the endomorphisms b satisfying b^2 = b. The extra generators are characterised in each case.